2018
DOI: 10.1111/voxs.12460
|View full text |Cite
|
Sign up to set email alerts
|

The relation between blood donor recruitment and donor diversity and loyalty in the Netherlands

Abstract: ConclusionOur results showed proportional differences in how people from different sex, age and ethnicity are recruited, and how recruitment relates to donor loyalty. We advocate for more personalized, evidence-based recruitment and retention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 26 publications
0
11
0
Order By: Relevance
“…In agreement with an earlier Swedish study [8], the results point to social norms and the importance of having a relative, friend or colleague inspiring donation, or even bringing donors to the centre. In the Netherlands as well, it was found that young men were most often recruited by other donors [7]. The simple fact of being healthy was the second most common reason, pointing to strong prosocial motivation and collectivism.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…In agreement with an earlier Swedish study [8], the results point to social norms and the importance of having a relative, friend or colleague inspiring donation, or even bringing donors to the centre. In the Netherlands as well, it was found that young men were most often recruited by other donors [7]. The simple fact of being healthy was the second most common reason, pointing to strong prosocial motivation and collectivism.…”
Section: Discussionmentioning
confidence: 99%
“…These include availability of donation sites, convenience/inconvenience, time waiting for donation, earlier transfusions in the family, media alerts, free health checks, the feeling of 'warm glow' and fear of needles. These factors reflect motivators such as social norms, reciprocity, personal moral norms, collectivism and other motivators [4][5][6][7].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations